CdS Quantum Dots Sensitized 2D La2Ti2O7 Nanosheets as Support for Visible Light‐Assisted Electrocatalytic Methanol Oxidation in Alkaline Medium. Issue 3 (6th March 2019) - Wang, Yuan; Hu, Jiayue; Zhai, Chunyang; Gao, Haifeng; Liu, Zhao-Qing; Du, Yukou; Zhu, Mingshan
Abstract : The heterojunction of cadmium sulfide (CdS)/La2 Ti2 O7 (CdS/LTO) attracts great attention in the application of photocatalysis. Here, it is used as a visible light–activated support and extends to the application of direct methanol fuel cells (DMFCs). First, uniform CdS quantum dots (QDs) are deposited on the surface of 2D perovskite‐type LTO nanosheets to form the CdS QDs/LTO heterojunction. Then, Pt electrocatalysts are deposited on the as‐prepared CdS QDs/LTO heterojunction and used as a working electrode for the application of the methanol oxidation reaction (MOR). With the assistance of visible light irradiation, the as‐prepared electrode shows 2.2 times enhanced activity toward MOR than that under the dark condition. Moreover, compared to Pt on the surface of LTO, the introduced CdS QDs not only improve the electrode's visible light response, but also facilitate charge separation via a type II heterojunction structure. This work provides a new insight into the development of highly efficient CdS/La2 Ti2 O7 for applications in DMFCs and beyond. Abstract : Cadmium sulfide quantum dots/La2 Ti2 O7 is used as a visible light–activated support, and it is extended to the application of anode reaction in direct methanol fuel cells. With the assistance of visible light irradiation, the as‐prepared electrode shows 2.2 times enhanced activity toward methanol oxidation than that under the dark condition.